Late gadolinium enhancement is a risk factor for major adverse cardiac events in unrecognised myocardial infarction without apparent symptoms: a meta-analysis. Issue 1 (January 2021) - Yang, Z.; Fu, H.; Li, H.; Wang, J.-R.; Xu, H.-Y.; Xie, L.-J.; Yang, M.-X.; Zhang, L.; Yang, Z.-G.; Guo, Y.-K.
Abstract : AIM: To assess the prognostic role of unrecognised myocardial infarction (UMI) detected at late gadolinium enhancement cardiac magnetic resonance imaging (LGE-CMRII). MATERIALS AND METHODS: Electronic databases including PubMed, EMBASE, Medline, and Cochrane were searched systematically for studies exploring the predictive value of UMI detected by LGE-CMRI for major adverse cardiac events (MACEs) and all-cause mortality in patients without apparent symptoms. Pooled hazard ratios (HRs) along with their 95% confidence intervals (CIs) were obtained from a random-effects model. Subgroup analyses were performed according to the different participants and outcomes. RESULTS: Eight studies (2, 009 participants) were identified comprising 442 patients with UMI detected at LGE-CMRI and 1, 567 without UMI. The presence of UMI on LGE was associated with a significantly increased risk for MACEs (HRs: 3.44, 95% CI: 2.06 to 5.75; p< 0.001) and all-cause mortality (HRs: 2.43, 95% CI: 1.00 to 5.87; p= 0.05). In the subgroup analysis, the presence of UMI on LGE remained significantly associated with the risk of MACEs in patients with suspected coronary artery disease (HRs: 3.82, 95% CI: 2.49 to 5.85; p< 0.01) and diabetes mellitus (HRs: 4.97, 95% CI: 3.02 to 8.18; p< 0.01). CONCLUSION: The presence of UMI detected by LGE-CMRI is associated with an increased risk of MACEs and all-cause mortality in patients without symptoms. LGE-CMRI could provide important prognostic information and guide risk stratification in patients with UMI. Highlights: The presence of UMI on LGE-CMR is associated with an increased risk of MACEs. UMI detected by LGE-CMR could be a valuable marker in risk stratification. LGE is an effective tool for providing prognostic information in patients with UMI.